2008
DOI: 10.1128/mcb.01921-07
|View full text |Cite
|
Sign up to set email alerts
|

DEK Is a Poly(ADP-Ribose) Acceptor in Apoptosis and Mediates Resistance to Genotoxic Stress

Abstract: DEK is a nuclear phosphoprotein implicated in oncogenesis and autoimmunity and a major component of metazoan chromatin. The intracellular cues that control the binding of DEK to DNA and its pleiotropic functions in DNA-and RNA-dependent processes have remained mainly elusive so far. Our recent finding that the phosphorylation status of DEK is altered during death receptor-mediated apoptosis suggested a potential involvement of DEK in stress signaling. In this study, we show that in cells committed to die, a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
163
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(183 citation statements)
references
References 65 publications
19
163
1
Order By: Relevance
“…Upregulation of DEK was involved in the p53/mouse double minute, B-cell lymphoma 2 family, and caspase signaling pathways (26). Notably, certain studies have revealed that DEK expression is associated with resistance to chemotherapeutic drugs, such as camptothecin, etoposide, neocarzinostatin and doxorubicin, which is often used to treat breast cancer (21,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of DEK was involved in the p53/mouse double minute, B-cell lymphoma 2 family, and caspase signaling pathways (26). Notably, certain studies have revealed that DEK expression is associated with resistance to chemotherapeutic drugs, such as camptothecin, etoposide, neocarzinostatin and doxorubicin, which is often used to treat breast cancer (21,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…DEK is a putative oncoprotein associated with tumor-initiating activity and regulates the transcriptional modifiers expression DEK encodes a nuclear protein that has been reported to exhibit a wide range of nuclear function; it modifies the topological conformation of DNA at replication or transcription (Alexiadis et al, 2000;Gamble and Fisher, 2007), affects histone acetylation and the RNA splicing machinery (Ko et al, 2006;Soares et al, 2006), positively and negatively regulates transcription (Fu et al, 1997;Campillos et al, 2003;Sammons et al, 2006), and is implicated in DNA damage response (Kappes et al, 2008). DEK expression is regulated by E2F and overexpression of DEK protein has been reported in several types of solid tumor (Carro et al, 2006).…”
Section: Molecular Classification Of Pulmonary Endocrine Tumorsmentioning
confidence: 99%
“…20,[33][34][35][36][37] DEK is a highly modified protein, containing 57 potential phosphorylated sites and over 70 lysine residues with the potential to be poly ADPribosylated and ubiquitinated. 26,27,[38][39][40] Such modifications alter its ability to bind chromatin, re-localize, and carry out specific biological functions in a manner that remain poorly understood and have been studied primarily in cancer cells wherein DEK is over-expressed. 41 For example, DEK is phosphorylated by CK2 during interphase and phosphorylation levels appear to peak in G1.…”
Section: Introductionmentioning
confidence: 99%